2017
DOI: 10.1016/j.livsci.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with arginine on haematological indices, serum chemistry, carcass yield, gut microflora, and lymphoid organs of growing turkeys

Abstract: W. 2017. Effect of dietary supplementation with arginine on haematological indices, serum chemistry, carcass yield, gut microflora, and lymphoid organs of growing turkeys. A 8-wk feeding experiment was conducted to investigate the effect of dietary supplementation 25 with Arg on haematological indices, serum chemistry, carcass yield, gut microflora, and 26 lymphoid organ weights of growing turkeys. A total of one hundred and eighty 56-d-old male 27 grower turkeys were weighed individually and randomly assigned… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 53 publications
3
30
1
Order By: Relevance
“…Nutrition is the most prominent factor affecting the gastrointestinal microbial community (Tomasello et al, 2014). As a novel finding of the present experiment, in ovo injection of l-arginine increased chickens' cae- (Oso et al, 2017). It was reported that dietary arginine improved intestinal absorption, barrier function and immune responses, but suppressed colonization of Clostridium perfringens in necrotic enteritis-challenged broilers (Muğlali et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
See 4 more Smart Citations
“…Nutrition is the most prominent factor affecting the gastrointestinal microbial community (Tomasello et al, 2014). As a novel finding of the present experiment, in ovo injection of l-arginine increased chickens' cae- (Oso et al, 2017). It was reported that dietary arginine improved intestinal absorption, barrier function and immune responses, but suppressed colonization of Clostridium perfringens in necrotic enteritis-challenged broilers (Muğlali et al, 2016).…”
Section: Discussionsupporting
confidence: 52%
“…Although there are no reports regarding the impact of in ovo injection of arginine on gut microflora community, in ovo injection of arginine improved the barrier functions of intestinal mucosa (Gao et al, 2017). However, caecal Coliform, Clostridium and Salmonella counts were not affected by dietary arginine supplementation (Oso et al, 2017). It was reported that male grower turkeys, which received higher dietary arginine levels (addition of 0.5 and 1 g arginine per kg of diet), had lower Salmonella counts in their small intestine, while higher caecal Lactobacillus counts and small intestinal Clostridium and Coliform counts (Oso et al, 2017).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations